2021
DOI: 10.12688/f1000research.27089.2
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of cross reactivity among phospholipases from Hymenoptera species

Abstract: Background: Phospholipases are enzymes with the capacity to hydrolyze membrane lipids and have been characterized in several allergenic sources, such as hymenoptera species. However, cross-reactivity among phospholipases allergens are little understood. The objective of this study was to determine potential antigenic regions involved in cross-reactivity among allergens of phospholipases using an in silico approach. Methods: In total, 18 amino acids sequences belonging to phospholipase family derived from speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Despite the several reported successful prediction story of allergenic proteins, there is some limitation associated (selection of scoring function, issue in considering the flexibility of ligand and receptor molecules, solvation effect) with computational docking and simulations algorithm and it is strongly recommended to validate the prediction using in vitro and/or in vivo assays (31). To date, no In-silico studies exploring IgEmediated honey bee allergies have been reported so far in the world and the Ha'il region of Saudi Arabia (32). There have already been some studies related to the molecular genetics of honey bees (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the several reported successful prediction story of allergenic proteins, there is some limitation associated (selection of scoring function, issue in considering the flexibility of ligand and receptor molecules, solvation effect) with computational docking and simulations algorithm and it is strongly recommended to validate the prediction using in vitro and/or in vivo assays (31). To date, no In-silico studies exploring IgEmediated honey bee allergies have been reported so far in the world and the Ha'il region of Saudi Arabia (32). There have already been some studies related to the molecular genetics of honey bees (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…When carrying out the alignment, it was considered that the sequences were different and came from different sources; therefore, the alignment parameters were set to utilize the BLOSUM62 matrix, which primarily assesses evolutionary divergence, along with adjustments to the conditional scoring matrix. 15,16 Phylogenetic analysis To construct the phylogenetic tree, we conducted a study using "Molecular Evolutionary Genetic Analysis" (MEGA) version 11 program. We employed the neighbor-joining (R) reconstruction method, supported by 100 bootstrap repetitions, to ensure the reliability and robustness of the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Branch length summation (SBL) was presented as a measure of overall comparison and homologies, providing insights into the number of nodes, their positions, and the formation of the evolutionarily closest sequence "clusters. 15,17 3D models of proteins Aquaporin models were acquired from the Protein Data Bank and AlphaFold (Homo sapiens, Felis catus, Equus caballus, Bos taurus, Mus musculus, Malassezia sympodialis, Saccharomyces cerevisiae, Penicillium chrysogenum, Escherichia coli). For A. fumigatus and Cannis lupus familiaris aquaporin 3D structures were modeled by homology using the Swiss Model server (https://swissmodel.expasy.org/), and these models were refined in ModRefiner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation